Characterization of Particle and Gaseous Emissions from Marine Diesel Engines with Different Fuels and Impact of After-Treatment Technology - Jinxi Zhou; Song Zhou; Yuanqing Zhu (Energies, 2017)
The International Maritime Organization (IMO) Marine Environment Protection Committee (MEPC) and some countries have gradually strengthened the laws regulating ship exhaust emissions. The aim of this paper is to estimate the impact of an after-treatment technology exhaust gas cleaning (EGC) system on marine diesel engine emissions and the cost advantage compared to using low-sulfur fuel oil. The emission characteristics of SO2 and particulate matter (PM) produced from high sulfur oil and low sulfur oil in a low-speed two-stroke marine diesel engine were also presented. The removal efficiency of SO2 has been tested and the PM removal efficiency was also predicted in this study. When using high sulfur oil, the emission factor of SO2 and PM were from 8.73 g/kWh to 11.6 g/kWh and 2.0 g/kWh to 2.7 g/kWh, respectively. These values are significantly higher than the emission values from using low sulfur oil. The fuel sulfur content (FSC) was the key factor affecting the emission factors of SO2 and PM. The fuel change could reduce the mass emission factor of PM, which is above 90% for the total particle emission with the two fuels. When using the EGC system, the desulfurization efficiencies were above 99%. The pH values at a 25, 39, 53, and 67% load were also stabilized to be around 7.5, 7.6, 7.7, and 8, respectively. The EGC system can also capture part of the primary PM and secondary PM formed from SO2. The EGC system was more effective for PM of the size larger than 1 μm. Thus, according to this study, the usage of low sulfur oil and EGC will also substantially decrease the emission of currently unregulated hazardous chemical species in the exhaust gas of ships in addition to satisfying future emissions regulations of ship. Furthermore, the EGC system also had a significant cost advantage compared to using low-sulfur fuel oil.